Congenital Insensitivity to Pain - Kundapur, Deeksha; Yu, Sheila; Mohanraj, Sylvia (The Meducator, 2018)
Pain is an essential sensation that has developed in complex organisms as an evolutionary mechanism to signal impending danger. Without pain, day-to-day functions become incredibly compromised. Pain is responsible for triggering the adoption of protective behaviours, such as physical withdrawal from painful stimuli to for tissue protection. Hereditary sensory and autonomic neuropathy type V (HSAN V), generally known as congenital insensitivity to pain (CIP), is a rare autosomal recessive sensory neuropathy. It is caused by defective nociceptive mechanisms, which result in an inability to experience pain. HSANs range from type I to type V, encompassing varying degrees of sensory impairment at each level. Only a handful of individuals experience the clinical symptoms associated with HSAN V, as it is the rarest of the HSAN disorders.